Rethinking the past to manage the future: Participating in complex contexts informed by biblical perspectives - Gous, Ignatius G. P. (HTS teologiese studies, 2021)
Change is the new normal, but so it has been for ages. Experience to navigate change is something you get just after you needed it, unless you tap into age-old experience. The Fourth Industrial Revolution (4IR) is bringing about wide-ranging changes. With people having to adjust, the question is whether Christianity, with its roots in preindustrial times, may support people to navigate these changes. This conceptual article focusses on the relationships amongst constructs, exploring logical arguments about how these constructs are associated. The 4IR is briefly described from differing vantage points, as to whether it is a valid description thereof. Whether a revolution or evolution, it is a complex system, and therefore the theory of complex systems is used, with the conclusion that one may merely participate in such systems. Being novel situations, one needs to participate creatively, based on a cognitive understanding of creativity. Creative solutions do not materialise out of thin air but are the novel use of existing knowledge structures. Christian traditions include institutional memories of how people managed situations of radical change, as reflected in Genesis 1 and Lamentations 4. These passages provide building blocks that may be used in creative coping strategies during times of change. Both passages suggest the strategy to juxtapose order and chaos, and borrowing from that, a ‘Grip-Grapple-Grow’ scaffolding system is suggested. To test the usability thereof, the issue of face masks during the Coronavirus Disease 2019 pandemic was touched upon, to evaluate how the interplay amongst 4IR, disruption, (Christian) beliefs and technological advancement may play out.Contribution: The Fourth Industrial Revolution is speeding up the pace of change, with people having to adapt. This article explores processes of change management, juxtaposing the theory of complex systems, the cognitive science understanding of creativity and institutional memories afforded by some Christian traditions reflecting on how people managed order and chaos.